Protein Kinases and Their Inhibitors in Pluripotent Stem Cell Fate Regulation - Jungwoon Lee; Young-Jun Park; Haiyoung Jung (Stem Cells International)
Protein kinases modulate the reversible postmodifications of substrate proteins to their phosphorylated forms as an essential process in regulating intracellular signaling transduction cascades. Moreover, phosphorylation has recently been shown to tightly control the regulatory network of kinases responsible for the induction and maintenance of pluripotency, defined as the particular ability to differentiate pluripotent stem cells (PSCs) into every cell type in the adult body. In particular, emerging evidence indicates that the balance between the self-renewal and differentiation of PSCs is regulated by the small molecules that modulate kinase signaling pathways. Furthermore, new reprogramming technologies have been developed using kinase modulators, which have provided novel insight of the mechanisms underlying the kinase regulatory networks involved in the generation of induced pluripotent stem cells (iPSCs). In this review, we highlight the recent progress made in defining the roles of protein kinase signaling pathways and their small molecule modulators in regulating the pluripotent states, self-renewal, reprogramming process, and lineage differentiation of PSCs.